Do metal objects such as mobile phones increase lightning risk? - Gomes C.; Khurshid Z.M. (Taylor and Francis Ltd., 2023)
Cellular telephones; Lightning; Spheres; Comsol multiphysics; Direct lightning; Direct lightning strikes; Direct strike; Human being; Human bodies; Lightning risk; Metal spheres; Metals